Sudden sensorineural hearing loss as the initial symptom in patients with acoustic neuroma - Song, Mengtao; Wang, Dayong; Li, Jin; Chen, Guohui; Zhang, Xiaolong; Wang, Hongyang; Wang, Qiuju (Frontiers in Neurology, 2022)
Background: Previous studies have shown that patients with acoustic neuroma (AN) sometimes present with sudden sensorineural hearing loss (SSNHL) as an initial symptom. The purpose of this research was to investigate the clinical characteristics, diagnosis and treatment of AN in patients diagnosed as SSNHL initially. Materials and Methods: We reviewed retrospectively medical records of all patients treated as SSNHL initially and diagnosed as AN finally after undergoing MRI, who were admitted to our hospital between 2008 and 2021. Patient demographics, associated complaints (mostly tinnitus and vertigo), severity of hearing loss, audiogram configurations, auditory brainstem response (ABR) and MRI examination were reviewed and analyzed. Treatment outcome and management protocols were also included in this study. Results: A total of 10 (0.7%, 10/1383) patients presented with SSNHL as the initial symptom and diagnosed as AN by magnetic resonance imaging (MRI) finally. Of the 10 patients enrolled in this study, four were male and six were females. Average age at time of diagnosis of SSNHL was 46.2 ± 13.16 years. These patients exhibited varying severity of hearing loss and a variety of audiogram configurations. All patients showed an abnormal ABR. According to the Koos grading standard, there were 5 grade I (intracanalicular) tumors, 3 grade II tumors and 2 grade III tumors. The treatment outcome revealed that 2 patients exhibited recovery of the average hearing of impaired frequency by more than 15 dB, and 6 patients showed no recovery. Four patients were referred to undergo surgical treatment after being diagnosed with AN, 1 patient accepted stereotactic radiation therapy, and the remaining 5 patients were taken “waiting and scan” strategy. Conclusions: The hearing loss of AN patients presented with SSNHL may improve with drug treatment. Hearing recovery for SSNHL does not exclude the presence of AN and all patients diagnosed as SSNHL initially should undergo MRI and ABR to prevent misdiagnosis and delays in potential treatment.